Pembelajaran Berbasis Geopark dengan Pemanfaatan Museum 13 Sebagai Pembelajaran Kreatif Berbasis Potensi Lokal di SDN Panjunan II Kalitidu - Susanti, Susi; Suprayitno; Andriyati, Alif; Nugroho, Febri Setyo (CV. Kurnia Grup, 2025)
Geopark-based learning is a contextual learning approach that utilizes the potential of the environment as a source of learning. SDN Panjunan II Kalitidu has a unique feature in the form of Museum 13, which is directly integrated with the school environment and the Bojonegoro geopark area. This study aims to describe the implementation of geopark-based learning through the use of Museum 13 as creative learning based on local potential at SDN Panjunan II Kalitidu. This study uses a descriptive qualitative approach with a case study design. Data collection was carried out through literature study, document study, and semi-structured interviews with the principal and teachers. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested using source triangulation. The results showed that geopark-based learning at SDN Panjunan II was implemented in an integrated manner at the stages of learning planning, LKPD preparation, evaluation, and extracurricular activities related to archaeology. The use of Museum 13 was able to realize contextual, authentic, and meaningful learning, as well as encourage the development of critical, analytical, and collaborative thinking skills and student learning awareness in accordance with the principles of deep learning and constructivism. In addition, geopark-based learning increases learning motivation, science literacy, and fosters concern for the preservation of local geological, historical, and cultural heritage. Thus, Museum 13 plays a strategic role as a source of contextual learning based on local potential in elementary schools.